Analysis of the Development of Micro, Small, and Medium Enterprises (MSMEs) Before and After Receiving Murabaha Financing from PT BPRS Rahmah Hijrah Agung Kota Lhokseumawe (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to analyze the development of Micro, Small, and Medium Enterprises (MSMEs) before and after receiving Murabaha financing from PT BPRS Rahmah Hijrah Agung. MSMEs play a crucial role in Indonesia’s economy, significantly contributing to community development and job creation. However, they often face various challenges, particularly in accessing financing. The Murabaha financing offered by BPRS, a sharia financial institution, provides an alternative for MSMEs to obtain business capital without the burden of high interest rates and complicated requirements typically associated with conventional banks. This research examines the differences in sales turnover, order volume, market reach, product quality, business profits, employment opportunities, financial management, and competitive ability of MSMEs before and after receiving financing from BPRS. The data used in this study is sourced from MSMEs that have received Murabaha financing during the period of 2020-2023. The research findings indicate a significant improvement in various aspects studied after MSMEs received Murabaha financing. These results suggest that the sharia financing products from BPRS play a crucial role in supporting the growth of MSMEs in Indonesia, particularly in enhancing their business capacity and competitiveness in the market. This study also highlights the importance of socialization and education regarding sharia financing products to improve MSME actors’ understanding of the available financing options.